Improvement of Ribbed Smoked Sheet (RSS) Production Effectiveness and Efficiency Using Total Productive Maintenance (TPM) Concept on Sheeter Machine - Effendi, Usman; Juwita, Niken Yulia Anjas (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractThis study aims to measure the sheeter machine's effectiveness, efficiency, and decline factors. Also, recommendations for improvement are made to counteract the decrease in RSS production efficiency. Overall Equipment Effectiveness (OEE) and Total Equipment Efficiency (TEE) were used to measure the effectiveness and efficiency of the machine. The Failure Method Effect Analyze (FMEA) is used to investigate machine failure, while TPM provides recommendations for improvement. The results showed that the sheeter machine effectiveness value in one year was almost entirely above the international standard at 85%, except for April and May at 72.27% and 80.33%. Furthermore, the highest and lowest TEE value was in February and April with 86.29% and 58.11%, respectively. According to the Six Big Losses calculations, the causes of a decrease in the effectiveness and efficiency of the sheeter machine were breakdown, setup, and adjustment losses, and idling, and minor stoppages. The failures with the highest Risk Priority Number (RPN) based on the FMEA were rusty bearings and halted machines resulting from tucked sheets under the roller. Minimizing Six Big Losses and adopting an autonomous maintenance system were two recommendations based on the TPM concept for increasing the efficacy and efficiency of RSS manufacturing.Keywords: machine efficiency, maintenance, sheet rubber AbstrakTujuan Penelitian ini adalah untuk mengukur nilai efektivitas, efisiensi dan mengidentifikasi faktor-faktor penyebab dasar penurunan efisiensi produksi pada mesin sheeter. Rekomendasi perbaikan diberikan untuk mengatasi penurunan efisiensi produksi RSS. Overall Equipment Effectiveness (OEE) dan Total Equipment Efficiency (TEE) digunakan untuk mengukur efektivitas dan efisiensi mesin. Analisis penyebab kegagalan mesin dilakukan menggunakan Failure Method Effect Analyze (FMEA), sedangkan rekomendasi perbaikan diberikan berdasarkan konsep TPM. Hasil penelitian menunjukkan bahwa nilai efektivitas mesin sheeter dalam satu tahun hampir keseluruhan berada di atas nilai standar internasional (85%) kecuali pada bulan April (72,27%) dan bulan Mei (80,33%). Nilai TEE pada mesin sheeter tertinggi terjadi pada bulan Februari (86,29%) dan terendah pada bulan April (58,11%). Hasil perhitungan Six Big Losses menunjukkan bahwa penyebab penurunan efektivitas dan efisiensi mesin sheeter adalah breakdown losses, setup and adjusment losses, dan idling and minor stoppages. Kegagalan yang memiliki nilai Risk Priority Number (RPN) tertinggi berdasarkan FMEA adalah bearing yang berkarat dan mesin yang berhenti karena sheet yang terselip di bawah roller. Rekomendasi perbaikan untuk meningkatkan efektivitas dan efisiensi produksi RSS berdasarkan konsep TPM adalah meminimalkan Six Big Losses dan menerapkan sistem pemeliharaan mandiri (autonomous maintenance).Kata kunci : efisiensi mesin, karet lembaran, perawatan